Analisis Strategi Pengembangan Agrowisata - Sandryas Alief Kurniasanti (Diploma Travel Business, Faculty of Social and Political Science, Jember University, 2019)
Abstract This research aims to analyze and identify the internal and external factors and to formulate the most suitable and signficant strategy for the agrotourism. The methods of data analysis and processing used are IFE, EFE, IE, SWOT, and AHP matrices. The result of this study shows that there are 10 internal and 9 external factors which lead into 9 alternative strategies. The strategy priority obtained are 2 strategy priorities the improvement of skills of human resources through assistance, pilotage, and training for farmers and farmers groups, derivative product diversification strategy created tangerine being pulpy orange and jam. Recommendations that could be done by strategy is create a program to develop human resources through the recruitment of labor who is expert, do routinely competency test of employees, as well as undertaking multi-sectoral coordination and cooperation. Keywords: Agrotourism, AHP, Development Strategy, SWOT, Tangerine